Increased Systemic Immune-Inflammation Index Is Associated With Delayed Cerebral Ischemia in Aneurysmal Subarachnoid Hemorrhage Patients - Chen, Liuwei; Pandey, Sajan; Shen, Rui; Xu, Yi; Zhang, Quanbin (Frontiers in Neurology, 2021)
Background: Systemic immune-inflammation index (SII) is a novel biomarker that reflects the state of a patient’s inflammatory and immune status. This study aimed to determine the clinical significance of SII as a predictor of delayed cerebral ischemia (DCI) in patients with aneurysmal subarachnoid hemorrhage (SAH). Methods: Retrospective data were collected from aneurysmal SAH patients who had been admitted to our hospital between January 2015 and October 2019. Both univariate and multivariate analyses were performed to investigate whether SII was an independent predictor of DCI. In addition, the receiver operating characteristic (ROC) curve and area under the curve (AUC) were also evaluated. Results: There were 333 patients with aneurysmal SAH included in this study. Multivariate logistic analysis revealed that a modified Fisher grade 3 & 4 score (odds ratio [OR]=7.851, 95% confidence interval [CI]: 2.312-26.661, P=0.001) and elevated SII (OR=1.001, 95%CI: 1.001-1.002, P<0.001) were independent risk factors for DCI. ROC curves showed that SII could predict DCI with an AUC of 0.860 (95%CI: 0.818-0.896, P<0.001). The optimal cut-off value for SII to predict DCI was 1424, an SII≥1424 could predict DCI with a sensitivity of 93.1% and a specificity of 68.1%. Patients with higher SII value on admission tended to have higher incidence of acute hydrocephalus and DCI, greater modified Fisher and Hunt-Hess scales, and poorer outcomes. Conclusions: SII is an independent predictor of DCI in patients with aneurysmal SAH. The SII system can be implemented in a routine clinical setting to help clinicians diagnose patients with high risk of DCI.